Perception of Individual Investors towards Stock Market Investments with Special Reference to Guwahati City - psgim, jcrm (Journal of Contemporary Research in Management (JCRM), 2023)
Capital is a crucial factor in the economic development. The economic development depends mainly on capital formation. As securities market grown-up individual investors directly invest their funds in financial securities. Thus, Investment is regarded as a critical aspect for financial planning and management. Investing in stock market for a retail investor is often risky. However, it can easily impel in the financial growth of an individual if the risk is well managed. Today stock market provide various avenues such as investment in equities, bonds, derivatives etc. Guwahati, the hub of northeast is rapidly growing in terms of population as well as economy. With the increase in the number of stock broking firms in Guwahati, there is a rise in the individual investors. This is also encouraging young investors to invest in various avenues. This research paper analyses the perception of retail investors of Guwahati city towards investment in various avenues of stock market.